2017
DOI: 10.21134/haaj.v17i2.323
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the evidence for the Theory of Planned Behavior: predicting heavy episodic drinking in Argentinean female and male youth

Abstract: Resumen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…According to a review of the TPB by Cooke et al (2016), intention was found to be the strongest predictor of actual behaviour. Intention has been reported to influence actual behaviour in alcohol-related studies including Zhang et al (2018) in South Africa, Peltzer et al (2017) in Argentina and Willis et al (2020) in Australia. Since previous studies focused on binge drinking, the present study aimed to investigate the influence of intention to quit on actual behaviour of quitting binge drinking.…”
Section: Intention To Quitmentioning
confidence: 99%
“…According to a review of the TPB by Cooke et al (2016), intention was found to be the strongest predictor of actual behaviour. Intention has been reported to influence actual behaviour in alcohol-related studies including Zhang et al (2018) in South Africa, Peltzer et al (2017) in Argentina and Willis et al (2020) in Australia. Since previous studies focused on binge drinking, the present study aimed to investigate the influence of intention to quit on actual behaviour of quitting binge drinking.…”
Section: Intention To Quitmentioning
confidence: 99%
“…Las y los adolescentes tienen cambios físicos, psicológicos y sociales durante esta etapa, también pueden presentar riesgos, vulnerabilidades y búsqueda de sensaciones que generan creencias sobre el CA como: mejora en el desempeño social, expresión de sentimientos, aceptación del grupo de referencia, alegría, ocio, relajación y estatus, que en su conjunto, determinan la actitud del consumo de riesgo (Martínez-Cardona et al, 2019;Patrick et al, 2010;Peltzer et al, 2017;Settles et al, 2014;Shell et al, 2010). Por otro lado, creencias negativas como: tener malas experiencias con la sedación, tener conflictos con la familia por consumir y meterse en problemas, son identificadas como factores de protección (Maggs et al, 2015).…”
Section: Introductionunclassified
“…Previous research employs TPB to understand the behavioural dynamics of substance abuse in general (Dempsey et al, 2016;Guzmán Facundo, García Salas, Aguilar, & Alonso Castillo, 2014;Moreta-Herrera, Ilaja-Verdesoto, Mayorga-Lascano, León-Tamayo & López-Castro, 2018b); as well as in alcohol consumption (Norman, 2011;Norman, Webb & Millings, 2019;Peltzer, Conde, Biscarra, Lichtenberger & Cremonte, 2017).…”
mentioning
confidence: 99%
“…This makes TPB quite useful when proposing scientific evidence about its results and practical applications in the areas of evaluation, diagnosis and intervention. Although studies of this model in Latin America are not widely systematized, abundant evidence (Dempsey et al, 2016;Mankarious & Kothe, 2015;Norman, 2011;Norman, Webb & Millings, 2019;Peltzer et al, 2017) (Sheeran et al, 2016;Wigg & Stafford, 2016).…”
mentioning
confidence: 99%